THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN PREVENTING BULLYING BEHAVIOR AT SCHOOL - Mustofa, Ahmad Soleh; Subakri, Subakri; Gunawan, Gunawan (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Bullying is a serious problem in the educational environment that can damage students' psychology and create an unhealthy learning atmosphere. As the main instrument in character education, Islamic Religious Education (PAI) has great potential to prevent and overcome bullying behavior. This study aims to analyze the role of PAI in building students' characters that respect the values of compassion, tolerance, and responsibility. A descriptive qualitative approach was used to understand the implementation of religious values in the context of formal education. Data were collected through classroom observation, interviews with PAI teachers, and curriculum analysis. The results showed that the implementation of Islamic values through PAI was able to increase students' empathy and create a harmonious school environment. The study also found that PAI teaching that is integrated with daily life is more effective than teaching methods that are only theoretical. The recommendations of this study include teacher training, curriculum updates, and community-based holistic approaches to support bullying prevention in schools.